Different interleukin‐17‐secreting Toll‐like receptor+ T‐cell subsets are associated with disease activity in multiple sclerosis. Issue 2 (26th December 2017) - Ferreira, Thais B.; Hygino, Joana; Wing, Ana Cristina; Kasahara, Taissa M.; Sacramento, Priscila M.; Camargo, Solange; Rueda, Fernanda; Alves‐Leon, Soniza V.; Alvarenga, Regina; Vasconcelos, Claudia Cristina; Agrawal, Anshu; Gupta, Sudhir; et al.
Summary: Signalling through Toll‐like receptors (TLRs) may play a role in the pathogenesis of autoimmune diseases, such as multiple sclerosis (MS). In the present study, the expression of TLR‐2, ‐4 and ‐9 was significantly higher on CD4 + and CD8 + T‐cells from MS patients compared to healthy individuals. Following in‐vitro activation, the proportion of interleukin (IL)‐17 + and IL‐6 + CD4 + and CD8 + T‐cells was higher in the patients. In addition, the proportion of IFN‐ γ ‐secreting TLR + CD8 + T‐cells was increased in MS patients. Among different IL‐17 + T‐cell phenotypes, the proportion of IL‐17 + TLR + CD4 + and CD8 + T‐cells producing IFN‐ γ or IL‐6 were positively associated with the number of active brain lesions and neurological disabilities. Interestingly, activation of purified CD4 + and CD8 + T‐cells with ligands for TLR‐2 (Pam3Csk4), TLR‐4 [lipopolysaccharide (LPS)] and TLR‐9 [oligodeoxynucleotide (ODN)] directly induced cytokine production in MS patients. Among the pathogen‐associated molecular patterns (PAMPs), Pam3Csk4 was more potent than other TLR ligands in inducing the production of all proinflammatory cytokines. Furthermore, IL‐6, IFN‐ γ, IL‐17 and granulocyte–macrophage colony‐stimulating factor (GM‐CSF) levels produced by Pam3Csk4‐activated CD4 + cells were directly associated with disease activity. A similar correlation was observed with regard to IL‐17 levels released by Pam3Csk4‐stimulated CD8 + T‐cells and clinical parameters. In conclusion, our data suggest that the expansion of different T helper type 17 (Th17) phenotypes expressing TLR‐2, ‐4 and ‐9 is associated with MS disease activity, and reveals a preferential ability of TLR‐2 ligand in directly inducing the production of cytokines related to brains lesions and neurological disabilities. Abstract : A high percentage of circulating TLR + T‐cells was observed in MS patients. Different TLR + Th17‐like phenotypes were positively associated with severity of MS. Th17‐related cytokines induced by TLR‐2 and ‐4 ligands were associated with MS severity.